Rectal foreign bodies: retained orange - Mulita, Francesk; Theofanis, George; Tchabashvili, Levan; Drakos, Nikolas; Maroulis, Ioannis (Gastroenterology Review/Przegląd Gastroenterologiczny, 2021)
Cases with rectal foreign bodies are no longer rare; however, epidemiological data even nowadays are lacking [1]. The first report was published in 1919, although cases have been described since the 16th century [2]. These patients usually present to the emergency department with complains of pelvic or lower abdominal pain [1]. Although there are a wide variety of types of foreign bodies and reasons for insertion, household objects such as bottles or glasses for autoeroticism is one of the most common reasons [2].